2018
DOI: 10.5152/istanbuljpharm.2017.0013
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the anticancer effects of Aloe vera and aloe emodin on B16F10 murine melanoma and NIH3T3 mouse embryogenic fibroblast cells

Abstract: Known for centuries as a "wonder" plant, Aloe vera (L.) Burm. f. has many biological and pharmacological activities. These effects are due to the variety of the chemical compounds including anthraquinones, glycoproteins, polysaccharides, vitamins and enzymes contained (Choi and Chung 2003; Du Plessis and Hamman 2014; Akev et al. 2015; Shrestha et al. 2015). Many of the medicinal effects have also been attributed to the immunomodulatory properties of the inner gel (Im et al. 2010), but it is also believed that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…In vivo studies in murine models have documented the antitumor and antioxidant properties of Aloe vera against Ehrlich carcinoma and ascites in distinct cancer lineages [ 140 ]. Other studies have shown positive results from the use of Aloe vera compounds, especially those derived from anthraquinones, in different cancer lineages, including lung, duodenum, prostate, breast, and colon cancers and melanomas.…”
Section: Advances and Challenges In The Use Of Aloe Vera ...mentioning
confidence: 99%
See 1 more Smart Citation
“…In vivo studies in murine models have documented the antitumor and antioxidant properties of Aloe vera against Ehrlich carcinoma and ascites in distinct cancer lineages [ 140 ]. Other studies have shown positive results from the use of Aloe vera compounds, especially those derived from anthraquinones, in different cancer lineages, including lung, duodenum, prostate, breast, and colon cancers and melanomas.…”
Section: Advances and Challenges In The Use Of Aloe Vera ...mentioning
confidence: 99%
“…Another issue is that AE, due to the presence of hydroxyl groups in its structure, has the potential to trigger some tumor-promoting activity. In vivo and in vitro studies conducted with substances possessing the same chemical nature have shown that many of these tumorigenic activities involve different biochemical pathways of the organism, such as DNA replication, modulation of oncogenes, and accumulation of mutations in the genetic code [ 48 , 140 , 141 ].…”
Section: Advances and Challenges In The Use Of Aloe Vera ...mentioning
confidence: 99%
“…Different modes of collaborative combination have been studied in several typical network environments as mentioned by Lehar et al (Lehár et al, 2007). Antitumor and cytotoxic potential of Barbadensis miller extract (BE) continues to be the center of interest for scientific research since 1980's and has extensively been used as an anticancer potential drug (Candoken et al, 2017) Marsdenia cundurango (Condurango), commonly known as condor vine. It is a medicinal plant whose bark extract ("mother tincture") is traditionally used in homeopathic medicines.…”
Section: Synergistic Effect Of Barbadensis Miller and Marsdenia Condumentioning
confidence: 99%
“…Aloe emodin's cytotoxicity in colon cancer cells is due to apoptosis (18). Also, the treatment of NIH3T3 cells with AVG may cause a delay in apoptosis (19). However, few studies have focused on the mechanism of Aloe vera cells in the HT29 cell lines.…”
Section: Introductionmentioning
confidence: 99%